Paleoclimatic reconstruction in the Tatra Mountains of the western Carpathians during MIS 9–7 inferred from a multiproxy speleothem record. Issue 1 (January 2021) - Błaszczyk, Marcin; Hercman, Helena; Pawlak, Jacek; Szczygieł, Jacek
Abstract: The SC-3 speleothem from Szczelina Chochołowska Cave, located in the Tatra Mountains, was studied in detail. U-series dating and age–depth modeling allowed us to constrain the period of speleothem growth to between approximately 330 and 200 ka, that is, during Marine Isotope Stages (MIS) 9–7. The complementary use of stable isotope analyses, petrographic studies, and trace element analyses allowed the identification of warm and wet climatic conditions that were favorable for speleothem growth during MIS 9e and MIS 9c. Unfavorable climatic periods included the cold glacial conditions of MIS 8 and the MIS 9/MIS 8 transition. The breaks in the growth of the SC-3 stalagmite were most likely connected with a reduction in precipitation in MIS 9a and extreme hydrologic events during MIS 8. Comparisons with other European records suggest that the climatic variability recorded in the speleothem from the Tatra Mountains is not only a record of local environmental conditions but can also be linked to European climatic patterns during both interglacial and glacial intervals. This makes our study the northernmost paleoclimatic record for the whole Carpathian range and one of the very few records from those periods worldwide.